PENJATUHAN SANKSI UNI EROPA ATAS TINDAKAN ANEKSASI RUSIA DI KRIMEA, UKRAINA - Ruth Intan Sari (Faculty of Law Universitas Sebelas Maret, 2021)
This study raises the issue of the legality of the imposition of European Union sanctions for Russia’s annexation of Crimea, Ukraine based on international law and the forms of imposing these sanctions. The method used in this research is normative legal research and is prescriptive. The types and sources of research data used are primary legal materials and secondary legal materials collected by using library research legal materials collection techniques. The data analysis technique used is a deductive mindset technique. This research results that the legality of EU sanctions is Council Decision 2014/512/CFSP and Council Regulation (EU) No. 833/2014 with provisions for imposing sanctions based on the European Union Agreement adopted within the framework of the Common Foreign Security and Policy (CFSP). The form of sanctions imposed are; (1) Arms embargo; (2) Export of dual-use goods; (3) Financial sanctions; (4) Prohibition of fulfilling claims; (5) Restrictions on services and other items.